Electrical power transmission system engineering analysis and design - Gonen, Turan (CRC Press/Taylor & Francis, 2014)
A hands-on electrical and mechanical design text for engineering students and practicing professionals, Electrical Power Transmission System Engineering: Analysis and Design, Third Edition features additional examples of fault analysis, a detailed discussion of flexible alternating current transmission systems, and expanded coverage of the structures, equipment, and environmental impact of transmission lines.